2017
DOI: 10.1111/and.12772
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency electromagnetic radiation from cell phone causes defective testicular function in male Wistar rats

Abstract: Cell phones have become an integral part of everyday life. As cell phone usage has become more widespread, concerns have increased regarding the harmful effects of radiofrequency electromagnetic radiation from these devices. The current study was undertaken to investigate the effects of the emitted radiation by cell phones on testicular histomorphometry and biochemical analyses. Adult male Wistar rats weighing 180-200 g were randomly allotted to control, group A (switched off mode exposure), group B (1-hr expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 14 publications
6
22
0
Order By: Relevance
“…Signifi cantly decreased LH in the EMR group suggested that cellphone radiation has a central effect on LH (hypothalamic or hypophyseal). Similar to the fi ndings of Meo et al, we also observed a considerable decrease of T levels (10,45), suggesting that cellphone waves had a negative effect on Leydig cells. That the treatment and control groups have close serum T levels also suggests that Egb761 protected Leydig cells from the cellphone EMR.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Signifi cantly decreased LH in the EMR group suggested that cellphone radiation has a central effect on LH (hypothalamic or hypophyseal). Similar to the fi ndings of Meo et al, we also observed a considerable decrease of T levels (10,45), suggesting that cellphone waves had a negative effect on Leydig cells. That the treatment and control groups have close serum T levels also suggests that Egb761 protected Leydig cells from the cellphone EMR.…”
supporting
confidence: 91%
“…Many factors, such as testicular torsion, infections, cryptorchidism, gonadal dysgenesis, varicocele, medication, and EMR can unfavorably affect spermatogenesis and lead to infertility (8). Chronic exposure to radiofrequency electromagnetic radiation of cell phone leads to defective testicular function that is associated with increased oxidative stress (9) and decreased gonadotropic hormones (FSH, LH, T) profi le (10).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, approximately 48.5 million couples suffer from infertility, and 20 to 30 per cent of them are due to male infertility without any known cause (Agarwal, Mulgund, Hamada, & Chyatte, 2015). Some studies confirmed that the nonthermal mechanism is the cause of the destructive effect of radiofrequency electromagnetic radiation (RF‐EMR) (Nizhelska, Marynchenko, & Piasetskyi, 2020), such as reactive oxygen species (ROS), which leads to lipid peroxidation and induction of oxidative stress (Oyewopo, Olaniyi, Oyewopo, & Jimoh, 2017) and apoptosis (Li et al., 2020). Malondialdehyde (MDA) is a final lipid peroxidation product that has toxic effects on tissues such as the kidney, liver, blood, heart, brain and spermatozoa after exposure to EMR (Adebayo, Adeeyo, Ogundiran, & Olabisi, 2019; Berköz et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…After a large dose of radiation for a long time, there may be atrophy of seminiferous tubules, reduction of spermatogenic cells, disorder of the arrangement, reduction of mature sperm and disorder of epidermal secretion. Study [10] shows long time exposure to mobile phone radiation rat gonadotropin decreased significantly, resulting in testicular dysfunction, increased oxidative stress, but also research shows that [11] RF radiation can significantly affect the sperm count and sperm deformity rate, but does not include sperm motility.…”
Section: Common Physical Chemical Natural Environmentmentioning
confidence: 99%